2020
DOI: 10.1039/c9ra08448g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an isatin derivative on tumor cell migration and angiogenesis

Abstract: Compound 5-61, a 5-(2-carboxyethenyl)isatin derivative was previously shown to have potent anticancer activity. Its effect on angiogenesis was further explored in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To detect the inhibitory action of both the complexes on cell migration of HepG2 cells, the scratch assay was carried out. [59][60][61] When treated with IC 50 of Pd(II) and Pt(II) complexes, cell migration of HepG2 was reduced in 12 h and 24 h. 62 The result also revealed that the number of cells was significantly reduced in the denuded area, suggesting that both the complexes could minimize the site-specific cell migration as well as trigger cell death (Fig. 5).…”
Section: In Vitro Cell Migration Studymentioning
confidence: 94%
“…To detect the inhibitory action of both the complexes on cell migration of HepG2 cells, the scratch assay was carried out. [59][60][61] When treated with IC 50 of Pd(II) and Pt(II) complexes, cell migration of HepG2 was reduced in 12 h and 24 h. 62 The result also revealed that the number of cells was significantly reduced in the denuded area, suggesting that both the complexes could minimize the site-specific cell migration as well as trigger cell death (Fig. 5).…”
Section: In Vitro Cell Migration Studymentioning
confidence: 94%
“…Tube forming treatment of tumor is a strategy aimed at tumor vascular system. Angiogenesis in adult individuals occurs under pathological conditions, such as during inflammation and the immune response, tumorigenesis, metastasis, and injury repair [ 22 ]. As shown in the Figure 4 E, HUVEC cells were inoculated on matrix gel at a density of 2 × 10 5 cells/mL.…”
Section: Resultsmentioning
confidence: 99%
“…This has given rise to very powerful and effective drugs such as the experimental drug Orantinib [ 43 , 44 ], the commercialized Sunitinib [ 45 ] or Nintedanib [ 46 ]. The transformations also were jointly carried out in positions 1 and 5, which have given rise to compounds with potent anti-neoplasic activity [ 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%